Association between retinol binding protein-4 and psoriasis vulgaris: a systematic review and meta-analysis - Gao, Guangcheng; Cui, Yuli; Cheng, Haiyan (Frontiers in Medicine, 2023)
Background Psoriasis vulgaris is a chronic skin disease which is related to cardiovascular and metabolic diseases. In the pathogenesis of these diseases, adipokines, including retinol binding protein-4 (RBP-4), play crucial roles. Studies have also shown that RBP-4 might be a meaningful factor in psoriasis however, relying on the analysis of a single study have some drawbacks. Objective To evaluate the association between RBP-4 and psoriasis vulgaris more comprehensively. Methods Six databases were searched to obtain relevant publications. The selection of the included studies was based on a criteria. The standardized mean difference (SMD) was used for analysis. A value of p < 0.05 was defined as significance. Results Seven studies were included, with 271 cases and 235 controls. In the comparison between patients and controls, the merged data suggested that levels of RBP-4 were significantly higher in patients (SMD = 0.61, 95%CI: 0.14, 1.07, p < 0.05). In five studies containing the data of RBP-4 levels before and after treatment, no significance was found, either for RBP-4 levels in the after-treatment group and control group in these five studies (p > 0.05). Subgroup analysis was conducted based on the therapy method. Patients with systematic treatment showed a significant decrease of BRP-4 level after the treatment (SMD = −0.64, 95%CI: −1.26, −0.03, p < 0.05). Conclusion For patients with psoriasis vulgaris, RBP-4 levels are elevated, and systematic treatment can lower these levels. RBP-4 might act as a key indicator for the diagnosis, efficacy assessment, and comorbidity monitoring of the patients. Further studies with well-designed protocols and enlarged populations are still needed.